Journals : vol. 2. - Chinzei, Yoshimi; Mizuta, Yuko; Mori, Chika (Tokyo : Museum of Contemporary Art, 2021)
Chim Pom ; Oiwa, Oscar ; Kawara, On ; Fluxus ; Mishima, Kimiyo ; Kwak, Duck Jun ; Kou, Kana (Yoshida, Kana) ; Ota, Saburo ; Taylor, Sam ; Kobayashi, Masato ; Weerasethakul, Apichatpong ; Boltanski, Christian
Journals vol. 2, Museum of Contemporary Art, Collection Gallery, Tokyo, 13 November 2021 - 23 February 2022
boek